2010
DOI: 10.1002/hipo.20846
|View full text |Cite
|
Sign up to set email alerts
|

GluK1 inhibits calcium dependent and independent transmitter release at associational/commissural synapses in area CA3 of the hippocampus

Abstract: CA3 pyramidal cells receive three main excitatory inputs: the first one is the mossy fiber input, synapsing mainly on the proximal apical dendrites. Second, entorhinal cortex cells form excitatory connections with CA3 pyramidal cells via the perforant path in the stratum lacunosum moleculare. The third input involves the ipsi-and contralateral connections, termed the associational/commissural (A/C) pathway terminating in the stratum radiatum of CA3, thus forming a feedback loop within this region. Since this e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Receptors for the metabotropic glutamate receptor, mGluR7, expressed at active zones facing interneurons but not principal cells (Shigemoto et al, 1996) specifically control the excitation of inhibitory cells (Scanziani et al, 1998). The kainate receptor GluK1, reduces release by effects on both Ca entry and on G-protein mediated stages in transmitter release (Salmen et al, 2012). In contrast, presynaptic NMDA receptors enhance Ca entry and facilitate release at some synapses made by CA3 collaterals(McGuinness L et al, 2010).…”
Section: Ca3 Pyramidal Cell Terminals: Numbers Form Contents Channmentioning
confidence: 99%
“…Receptors for the metabotropic glutamate receptor, mGluR7, expressed at active zones facing interneurons but not principal cells (Shigemoto et al, 1996) specifically control the excitation of inhibitory cells (Scanziani et al, 1998). The kainate receptor GluK1, reduces release by effects on both Ca entry and on G-protein mediated stages in transmitter release (Salmen et al, 2012). In contrast, presynaptic NMDA receptors enhance Ca entry and facilitate release at some synapses made by CA3 collaterals(McGuinness L et al, 2010).…”
Section: Ca3 Pyramidal Cell Terminals: Numbers Form Contents Channmentioning
confidence: 99%
“…The authors concluded that modulation of glutamate release by GluK1-containing KARs in the spinal cord depends on the activation of a G protein. In the hippocampus, ATPA (1 μM) decreased fEPSP amplitude and reduced calcium influx at excitatory synaptic terminals (Salmen et al, 2012), which was abolished by inactivation of G proteins with pertussis toxin.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, expression of GluK1 in SHSY5 neuroblastoma cells was sufficient to reconstitute metabotropic activity of KARs, as evaluated by the G protein and PKC activation inducing internalization of KARs from the membrane (Rivera et al, 2007). Recent experiments confirmed the involvement of GluK1 in the metabotropic control of glutamate release (Segerstrå le et al, 2010;Salmen et al, 2012). However, a biochemical interaction between GluK5 and a G aq protein was identified in biochemical experiments (Ruiz et al, 2005).…”
Section: A Receptor With Two Modes Of Signalingmentioning
confidence: 99%